The Influence of Embedded Finance, QRIS Usage, and Digital Financial Literacy on MSME Financial Resilience - Masyadi Masyadi; Mutmainna Andi Sudirman; Sukma Aini (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
This study examines the influence of embedded finance, QRIS usage, and digital financial literacy on the financial resilience of micro, small, and medium enterprises (MSMEs). The rapid development of financial technology has encouraged MSMEs to use digital financial services in their daily business activities, including integrated financial services, digital payments, and online financial platforms. However, the use of technology alone does not guarantee stronger business resilience if MSME owners do not have adequate financial knowledge and the ability to manage digital financial services effectively. This study focuses on MSMEs in Soppeng Regency, South Sulawesi, that have used QRIS or other digital financial services. A quantitative explanatory approach is used to test the relationship between the research variables. Data are collected through questionnaires distributed to MSME owners or managers, and the analysis is conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that embedded finance, QRIS usage, and digital financial literacy have positive effects on MSME financial resilience. Embedded finance helps MSMEs access financial services more easily, QRIS supports transaction efficiency and digital financial records, while digital financial literacy strengthens the ability of MSME owners to manage financial risks and make better decisions. Among the three variables, digital financial literacy shows the strongest contribution to financial resilience. This study contributes to the fintech and MSME literature by emphasizing financial resilience as the main outcome, rather than merely focusing on technology adoption. Practically, the findings suggest that MSMEs, fintech providers, financial institutions, and policymakers should strengthen digital financial literacy and encourage the strategic use of digital financial services to support MSME sustainability